5(-3+6n)=33+6n

Simple and best practice solution for 5(-3+6n)=33+6n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(-3+6n)=33+6n equation:


5(-3+6n)=33+6n

We simplify the equation to the form, which is simple to understand
5(-3+6n)=33+6n

Reorder the terms in parentheses
+(-15+30n)=33+6n

Remove unnecessary parentheses
-15+30n=+33+6n

We move all terms containing n to the left and all other terms to the right.
+30n-6n=+33+15

We simplify left and right side of the equation.
+24n=+48

We divide both sides of the equation by 24 to get n.
n=2

See similar equations:

| 12x^2-64=-x^4 | | 3bx-2=4ax+3 | | 7th-4=10t+14 | | -(2p+4)+8p=-p-18 | | -80+4y=4 | | 6-4r+3r=13 | | -7-3i+8-3i=0 | | 4w^2+4w+1=49 | | .5(x+40)+.1x=29 | | -8x+4=4 | | 16(x+1)=4(4x+9)-20 | | a/6+4a/8-1/3=a+3/4 | | 7x+20=-13 | | x+30=45 | | 7(2c-5)=6 | | 3(x-3)+5x=4(2x+4)-8 | | 65=5x+12 | | 7+y=-13 | | 72c-5=6 | | y-240=6(x-20) | | 4x+3-5=2x | | 4(y-5)(2y+3)=0 | | 26+(-16)+4= | | 11+3y=14 | | -(7x+3)-(-6x-8)=2 | | -1y=-20 | | 2p^2+4p-1=7p^2-7p+1 | | -3(4x-1)-3=-2(9x+11)-2 | | 1/4(x-3/8)=1/8 | | 3(2x+5)=2(3x-4) | | 1d/4=-2/4 | | -7+5y=-16 |

Equations solver categories